Malaysian vs Philippines news reports: a transitivity analysis of the Lahad Datu incident / Wan Faizatul Azirah Ismayatim, Sridevi Sriniwasss and Nadiah Thanthawi Jauhari - Ismayatim, Wan Faizatul Azirah; Sriniwasss, Sridevi; Jauhari, Nadiah Thanthawi (Universiti Teknologi MARA, 2018)
This paper reports on a study on Experiential meaning particularly the main process types used in the reporting of the airstrike event launched by Malaysian security forces on March 5, 2013 during the intrusion of “Sulu Sultan” followers in Lahad Datu. Data for the study comprised text reports pertinent to the airstrike event published in four different English newspapers which are The News Straits Times (NST), The Star (TS), The Philippine Daily Inquirer (TPDI) and The Philippine Star (TPS). A total of 8 texts were analysed. Various methods have been developed to study newspapers representation and stance of controversial issues which include content analysis, critical discourse analysis, lexical cohesion, the use of metaphors, transitivity and thematic analysis among others. However, the framework of transitivity has not been widely used. Hence, Systemic Functional Linguistics (SFL), in particular, the System of Transitivity propounded by M.A.K. Halliday (1994) was used to bridge the gap in research and the methodology of text analysis was deployed. The study revealed that NST was the only newspaper which highlighted the sorrow and the grief of Malaysians and its Prime Minister in which this newspaper accounts for the most in employing the Mental Processes, while TS, TPDI and TPS highlighted more on the physical actions and the resoluteness of both countries in handling the Lahad Datu conflict when Material Processes were dominant in these newspapers.